129k views
2 votes
If a^2+b^2=13 and ab =6 find the value of
(i)(2a+2b)
(ii)(2a-2b)

1 Answer

2 votes

Answer:

I)


2a + 2b = -10\text{ or } 2a + 2b = 10

II)


2a - 2b = -2 \text{ or } 2a-2b= 2

Explanation:

We are given that:


\displaytstyle a^2 + b^2 = 13 \text{ and } ab= 6

I)

Recall the perfect square trinomial pattern:


\displaystyle (a+b)^2 = a^2 + 2ab + b^2

Rewrite:


\displaystyle (a+b)^2 = (a^2 + b^2) + (2ab)

Substitute:


\displaystyle (a+b)^2 = (13) + (12)

Evaluate:


\displaystyle (a + b)^2 = 25

Take the square root of both sides:


\displaystyle a + b = \pm√(25) = \pm5

Hence:


\displaystyle 2a + 2b = \pm 10

Therefore:


\displaystyle 2a + 2b = -10 \text{ or } 2a + 2b = 10

II)

Likewise:


\displaystyle (a-b)^2 = a^2 - 2ab + b^2

Substitute:


\displaystyle (a-b)^2 = (13) -(12)

Solve:


\displaystyle \begin{aligned} (a-b)^2 &= 1 \\ a-b &= \pm √(1) \\ a-b &= \pm 1\\ 2a - 2b &= \pm 2\end{aligned}

In conclusion:


2a - 2b = -2 \text{ or } 2a-2b= 2

User Alex Kucherenko
by
5.1k points